السِّياق ودلالاته في فهم النَّص القرآني - Abdoul Karim Toure; Noornajihan Ja‘afar; Adnan Mohamed Yusoff; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya; Mesbahul Houqe; Berte Alassane (Universiti Sains Islam Malaysia, 2024)
This study aims to highlight some of the words mentioned in the Holy Qur’an which have more than one meaning, the study will mention these different meanings of each word in the uses of the Holy Qur’an which cannot be understood or difficult to know the exact meaning of the Qur’an among the many other meanings intended elsewhere except by understanding the context of the verses. The researchers adopted the inductive method in interpretation and analysis of the chosen word and elaborate in their study. The most important findings of the study are that the meanings and interpretation of the Qur'an is continuous for the successive generations, it is tender and inexhaustible for those scholars willing to interpret it base on Sharia principle.